2021
DOI: 10.33448/rsd-v10i14.22377
|View full text |Cite
|
Sign up to set email alerts
|

Positive fluid balance within the first 72 hours in the intensive care unit is associated with higher mortality in adult patients

Abstract: Objective: To identify the association between cumulative fluid balance in the first 72 hours of ICU stay and outcomes. Methodology: retrospective observational cohort with data analysis of adult patients hospitalized in an ICU of a tertiary teaching hospital. Results: a total of 86 patients who remained in the ICU for more than 72 hours were evaluated. The fluid balance in the first 72 hours was higher in the subgroup of patients who died in the ICU (5210.3 ± 2787.7 vs. 3017.4 ± 2847.2 mL, p = 0.004). The flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…regarding positive CFB within 72 hours of ICU care patients; the optimal cut-off value was 3900 ml (sensitivity 72.7%, specificity 65.1%) (13). de Oliveira et al reported that CFB greater than 3000 ml at 24 hours and 48 hours with a diagnosis of sepsis was an independent risk factor for mortality (14).…”
Section: Discussionmentioning
confidence: 99%
“…regarding positive CFB within 72 hours of ICU care patients; the optimal cut-off value was 3900 ml (sensitivity 72.7%, specificity 65.1%) (13). de Oliveira et al reported that CFB greater than 3000 ml at 24 hours and 48 hours with a diagnosis of sepsis was an independent risk factor for mortality (14).…”
Section: Discussionmentioning
confidence: 99%